2014
DOI: 10.2166/wst.2014.170
|View full text |Cite
|
Sign up to set email alerts
|

Removal of nitrogen from secondary effluent of a petrochemical industrial park by a hybrid biofilm-carrier reactor with one-stage ANAMMOX

Abstract: A laboratory study was undertaken to explore the capability of one-stage ANAMMOX in a hybrid biofilm-carrier reactor (HBCR) fed with petrochemical wastewater. Under favorable operating conditions in continuous-flow operations (at the dissolved oxygen level of 0.5-1.0 mg L(-1)), the average total nitrogen (TN) removal efficiency reached 62-67% and approximately 90% of TN can be removed by ANAMMOX. In batch operations of the hybrid biofilm-carrier reactor (without adding carbon substrate), the specific TN remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… observed up to 86% NRE in an anammox CSTR treating synthetic wastewater at various NLR (0.1-1.2 gN L -1 d -1 );Alavi et al (2011) reported a total nitrogen removal efficiency of 92.4% in an upflow anaerobic bioreactor (UABR) treating ammonium-rich wastewater produced by an ammonia plant, at similar applied NLR (0.45 gN L -1 d -1 );Lin et al (2014) observed a total nitrogen removal efficiency of 62-67% in a one stage anammox hybrid biofilmcarrier reactor (HBCR) treating petrochemical wastewater (NLR, 0.11-0.31 gN L -1 d -1 ).…”
mentioning
confidence: 99%
“… observed up to 86% NRE in an anammox CSTR treating synthetic wastewater at various NLR (0.1-1.2 gN L -1 d -1 );Alavi et al (2011) reported a total nitrogen removal efficiency of 92.4% in an upflow anaerobic bioreactor (UABR) treating ammonium-rich wastewater produced by an ammonia plant, at similar applied NLR (0.45 gN L -1 d -1 );Lin et al (2014) observed a total nitrogen removal efficiency of 62-67% in a one stage anammox hybrid biofilmcarrier reactor (HBCR) treating petrochemical wastewater (NLR, 0.11-0.31 gN L -1 d -1 ).…”
mentioning
confidence: 99%
“…Some studies have shown that Candida has a certain effect on the removal of nitrite from aquaculture water [41,42], but it requires a rich organic nutrient substrate in water. Therefore, the small fluctuation in the concentrations of NO 2 -N and NO 3 -N in the water is caused by microbial nitrification and denitrification.…”
Section: Removal Of Nitrite Nitrogen Nitrate Nitrogen Ammonia Nitromentioning
confidence: 99%